Linkage analysis of polymorphisms within the DNA fragment XJ cloned from the breakpoint of an X;21 translocation associated with X linked muscular dystrophy. Issue 6 (December 1986) - Thompson, M W; Ray, P N; Belfall, B; Duff, C; Logan, C; Oss, I; Worton, R G
Abstract : Cloning of a DNA segment including the translocation breakpoint in a female with an X;21 translocation and X linked muscular dystrophy has led to identification of three subclones which detect polymorphic markers. The alleles of these markers, XJ1 X 1, XJ1 X 2, and XJ2 X 2, are in strong linkage disequilibrium. Linkage analysis in 31 families with Duchenne or Becker muscular dystrophy has shown recombination within the XJ segment in one case, and recombination of DMD with both the XJ segment and the pERT87 segment in a second, but has revealed no recombination between the XJ and pERT87 segments. The XJ markers increase the proportion of DMD and BMD families that are informative for carrier detection and prenatal diagnosis, but in view of the risk of recombination they must be used with caution. The site(s) of the DMD mutation(s) relative to the XJ and pERT87 markers, and the detailed molecular structure of the DMD region, remain to be determined.